Rapid progression of aortic stenosis in a 3-month-old infant with bicuspid aortic valve and DeSanto-Shinawi syndrome - Daiji Takajo; Ghadir Katato; Sanjeev Aggarwal (Wolters Kluwer Medknow Publications, 2021)
A 3-month-old female was diagnosed at 1 month of age with DeSanto-Shinawi syndrome (DSS) and bicuspid aortic valve with trivial stenosis. The aortic valve stenosis progressed to severe within 2 months and required balloon aortic valvuloplasty. This is the first case of aortic stenosis (AS) associated with DSS, and the syndrome may be the reason for the rapid worsening of AS in this case.